Nonoperative Management of Minimally Displaced Lateral Compression Type 1 Pelvic Ring Injuries With and Without Occult Instability. Issue 6 (June 2022) - Parry, Joshua A.; Hadeed, Michael M.; Tucker, Nicholas J.; Strage, Katya E.; Scott, Bryan L.; Stacey, Stephen C.; Heare, Austin; Mauffrey, Cyril
Abstract : Objectives: To determine the association of pelvic fracture displacement on lateral stress radiographs (LSRs) with the hospital course of patients with minimally displaced lateral compression type 1 (LC1) pelvic injuries. Design: Retrospective review. Setting: Level 1 trauma center. Patients/Participants: Twenty-eight adult patients with minimally displaced (<1 cm) LC1 injuries. Intervention: Nonoperative management. Main Outcome Measurements: Delayed operative fixation, days to clear physical therapy, mobilization, hospital length of stay, and total hospital opioid morphine equivalent dose. Results: LSR displacement was correlated with delayed operative fixation [r = 0.23, 95% confidence interval (CI) 0.05–1.11; P = 0.01], days to clear PT (r = 0.13, CI 0.01–0.28; P = 0.02), length of stay (r = 0.13, CI 0.006–0.26; P = 0.02), and opioid morphine equivalent dose (r = 19.4, CI 1.5–38.1; P = 0.03). A receiver operating characteristic curve for delayed operative fixation over LSR displacement had an area under the curve of 0.87. The LSR displacement threshold that maximized sensitivity and specificity for detecting patients who required delayed fixation was 10 mm (100% sensitivity and 78% specificity). Ten of the 15 patients with ≥10 mm of displacement on LSRs underwent delayed operative fixation for pain with mobilization at a median of 6 days (interquartile range 3.7–7.5). Patients with ≥10 mm of displacement on LSRs took longer to clear PT, took longer to walk 15 feet, had longer hospital stays, and used more opioids. Conclusions: LC1 fracture displacement on LSRs is associated with delayed operative fixation, difficulty mobilizing secondary to pain, longer hospital stays, and opioid use. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.